RFID Instrumentation in a Field Application - Watkins, S.E.; Swift, T.M.; Molander, M.J. (2007 IEEE Region 5 Technical Conference, 2007)
The behavior of radio-frequency identification (RFID) tags is investigated in a field application. The RFID instrumentation is used to mark the position of point strain sensors in a fiber-reinforced polymer (FRP), short-span bridge. The tags are surface mounted on carbon FRP structural elements and covered with a resin wear layer, i.e. the deck of the bridge. The smart composite bridge was installed in 2000 and serves as a field testbed for various sensor technologies including the RFID tags. The operation of the RFID network is tested in the field and compared to laboratory tags. Specific research issues include long-term survivability after six years, behavior on carbon FRP material, and environmental effects of weather, especially the presence of water. The feasibility of short-range RFID tags as location markers is discussed. The results show the suitability of RFID technology for field environments.